2023
DOI: 10.1021/acsaem.2c03339
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Photodeposited RuOx for Alkaline Water Electrolysis

Abstract: The storage of renewable energy is a pressing challenge to overcome in the transition toward a power grid based on plentiful, yet intermittent energy supplies. The renewables-driven electrolysis of water to form hydrogen fuel is an attractive avenue, but requires better oxygen-evolution reaction (OER) catalysts to be feasible at scale. RuO 2 is touted as one of the superior OER catalysts but only under acidic conditions; RuO 2 electrocatalysts suffer from poor stability under alkaline conditions. In this work,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…The noble metals Ir/Ru are used as benchmark catalysts in electrolytic water separation technology. However, the high voltage required for OER and the slow kinetics hinders new catalyst development [139][140][141][142]. The unique structure and various anisotropies of amorphous materials provide new directions in the search for stable and efficient catalysts [143][144][145][146].…”
Section: Oxygen Evolution Reaction 521 Precious Metal-based Amorphous...mentioning
confidence: 99%
“…The noble metals Ir/Ru are used as benchmark catalysts in electrolytic water separation technology. However, the high voltage required for OER and the slow kinetics hinders new catalyst development [139][140][141][142]. The unique structure and various anisotropies of amorphous materials provide new directions in the search for stable and efficient catalysts [143][144][145][146].…”
Section: Oxygen Evolution Reaction 521 Precious Metal-based Amorphous...mentioning
confidence: 99%
“…12 The forward-looking work carried out by Cai et al revealed that an imine covalent organic framework (TAPB-PDA-COF) was selected as a host material to accommodate active sulfur, and that the performance of Li-S batteries could be regulated by changing the type of conductive additive, which encouraged researchers to explore more appropriate conductive additives. 13 In terms of sustainable energy conversion technology, processes such as water electrolysis, 14 electrochemical synthesis of hydrogen peroxide, 15 and research on fuel cells 16 are regarded as having practical application potential. In water electrolysis, the oxygen evolution reaction (OER) at the anode possesses a decisive role in transforming H 2 O to O 2 by acquiring electrons from the reaction system.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of sustainable energy conversion technology, processes such as water electrolysis, 14 electrochemical synthesis of hydrogen peroxide, 15 and research on fuel cells 16 are regarded as having practical application potential. In water electrolysis, the oxygen evolution reaction (OER) at the anode possesses a decisive role in transforming H 2 O to O 2 by acquiring electrons from the reaction system.…”
Section: Introductionmentioning
confidence: 99%